Directed energy deposition build process control effects on microstructure and tensile failure behaviour - Tan, Eddie Zhi’En (2022)
An investigation on the effects of additive manufacturing build strategy raster scan patterns on process control, microstructure, and mechanical properties is reported in this study. Although the effects of build orientation on the properties of AM-built components are well understood, the effects of build strategy on material and mechanical properties have yet to be explored in detail. This study looks into the effects of directed energy deposition build strategy on the materials and mechanical properties of Stainless Steel 316 L show interesting build strategy trends. Three different directed energy deposition raster scan strategies, namely: short unidirectional, bidirectional, and long unidirectional raster scan deposition patterns were evaluated. Tensile tests were conducted to characterise the variability in mechanical properties of the directed energy deposition built specimens compared to bar stock material properties. The results show different anisotropic properties for each build strategy. The highest tensile strength, yield stress, and fracture strain were observed for the long unidirectional raster scan build strategy, followed by the bidirectional and short unidirectional raster scan build strategies.